2017
DOI: 10.3389/fpsyg.2017.00771
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Upward Social Comparison and Self-esteem and the Moderating Role of Social Comparison Orientation in the Association between Social Networking Site Usage and Subjective Well-Being

Abstract: The increased pervasiveness of social media use has raised questions about potential effects on users’ subjective well-being, with studies reaching contrasting conclusions. To reconcile these discrepancies and shed new light on this phenomenon, the current study examined: (1) whether upward social comparison and self-esteem mediate the association between social networking site (SNS) usage and users’ subjective well-being, and (2) whether the association between SNS usage and upward social comparison is modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
175
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(190 citation statements)
references
References 56 publications
11
175
1
3
Order By: Relevance
“…Additionally, it is suggested that high social comparison orientation SNS users are more likely to engage in upward social comparisons, and therefore face more detrimental effects in regards to self-evaluations and well-being (Wang et al, 2017). Such findings support the need for further exploration in potential body image and media literacy interventions to educate individuals about the impact of comparisons on SNS and well-being .…”
Section: Mediating Factorsmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, it is suggested that high social comparison orientation SNS users are more likely to engage in upward social comparisons, and therefore face more detrimental effects in regards to self-evaluations and well-being (Wang et al, 2017). Such findings support the need for further exploration in potential body image and media literacy interventions to educate individuals about the impact of comparisons on SNS and well-being .…”
Section: Mediating Factorsmentioning
confidence: 71%
“…A total of 12 studies were highlighted to identify mediating factors (Ridolfi, Myer, Crowther & Ciesla, 2011;Tiggemann & Slater, 2013;Fardouly & Varanian, 2015;Hanna, Ward, Seabrook, Jeralds, Reed, Giaccardi & Lippman, 2017;Hendrickse et al, 2017;Rousseau, Eggermont & Frison, 2017;Stapleton, Luiz & Chatwin, 2017;Wang, Wang, Gaskin & Hawk, 2017;Choukas, Bradley, Nesi, Widman & Higgins 2018;Fardouly, Willburger & Vartanian, 2018;Feltman & Szymanski, 2018;Sherlock & Wagstaff, 2018). These studies comprised of predominantly female participants and included a samples from primary school (Tiggemann & Slater, 2013), university Chouckas et al, 2018), in addition to Ozone and WeChat users (Wang, Wang, Gaskin & Hawk, 2017) and Instagram users (Sherlock & Wagstaff, 2018).…”
Section: Mediating Factorsmentioning
confidence: 99%
“…However, the mechanisms underlying these associations need further investigation. In line with Wang, Wang, Gaskin, & Hawk (2017), we hypothesized to find that indicators of (intensity of) Facebook use would be linked to reduced well-being -as shown by elevated depressive-, anxiety-, and stress-related symptoms -via social comparison and self-esteem. For this purpose, we set up an exploratory study (Study 1), modeling the unique associations between each of these constructs.…”
Section: Discussion Of the Key Findingsmentioning
confidence: 92%
“…Self-esteem assesses an individual's perception of himself or herself (Fuller et al, 2006). In psychology, numerous studies have examined self-esteem and its connections with a person's cognition, emotions, and behavior (Wang et al, 2017). According to Fuller et al (2006), self-esteem refers to adolescents' evaluations of their own worth or their satisfaction with themselves, and is divided into three dimensions of the self: physical appearance, romantic attractiveness, and the ability to develop and keep close friendships.…”
Section: Social Value Of Luxury Brandsmentioning
confidence: 99%
“…According to Fuller et al (2006), self-esteem refers to adolescents' evaluations of their own worth or their satisfaction with themselves, and is divided into three dimensions of the self: physical appearance, romantic attractiveness, and the ability to develop and keep close friendships. Wang et al (2017) proposes that self-esteem refers to a comparatively steady mental state that reflects people's social reality and influences their cognition and behavior. People with high self-esteem tend to be more resilient to external influences than are those with low selfesteem.…”
Section: Social Value Of Luxury Brandsmentioning
confidence: 99%